Targeting Aberrant Expression of STAT3 and AP-1 Oncogenic Transcription Factors and HPV Oncoproteins in Cervical Cancer by Berberis aquifolium - Singh, Tejveer; Chhokar, Arun; Thakur, Kulbhushan; Aggarwal, Nikita; Pragya, Pragya; Yadav, Joni; Tripathi, Tanya; Jadli, Mohit; Bhat, Anjali; Gupta, Pankaj; Khurana, Anil; Chandra Bharti, Alok (Frontiers in Pharmacology, 2021)
Background: Present study examines phytochemical preparation that uses berberine’s plant source B. aquifolium root for availability of similar anti-cervical cancer (CaCx) and anti-HPV activities to facilitate repurposing of the B. aquifolium based drug in the treatment of CaCx. Purpose: To evaluate therapeutic potential of different concentrations of ethanolic extract of B. aquifolium root mother tincture (BAMT) against HPV-positive (HPV16: SiHa, HPV18: HeLa) and HPV-negative (C33a) CaCx cell lines at molecular ongenic level. Materials and methods: BAMT was screened for anti-proliferative activity by MTT assay. Cell cycle progression was analyzed by flow cytometer. Then, the expression level of STAT3, AP-1, HPV E6 and E7 was detected by immunoblotting whereas nuclear localization was observed by fluorescence microscopy. Phytochemicals reportedly available in BAMT were examined for their inhibitory action on HPV16 E6 by in silico molecular docking. Results: BAMT induced a dose-dependent decline in CaCx cell viability in all cell types tested. Flowcytometric evaluation of BAMT-treated cells showed a small but specific cell growth arrest in G1-phase. BAMT-treatment resulted in reduced protein expression of key transcription factors, STAT3 with a decline of its active form pSTAT3 (Y705); and components of AP-1 complex, JunB and c-Jun. Immunocytochemistry revealed that BAMT did not prevent the entry of remnant active transcription factor to the nucleus, but loss of overall transcription factor activity resulted in reduced availability of transcription factors in the cancer cells. These changes were accompanied by gradual loss of HPV E6 and E7 protein in BAMT-treated HPV-positive cells. Molecular docking of reported active phytochemicals in B. aquifolium root was performed, which indicated a potential interference of HPV16 E6’s interaction with pivotal cellular targets p53, E6AP or both by constituent phytochemicals. Among these, berberine, palmatine and magnoflorine showed highest E6 inhibitory potential. Conclusion: Overall, BAMT showed multi-pronged therapeutic potential against HPV infection and cervical cancer and the study described the underlying molecular mechanism of its action.